2002
DOI: 10.1103/physrevlett.88.033903
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Scarred Modes in Asymmetrically Deformed Microcylinder Lasers

Abstract: We report observation of lasing in the scarred modes in an asymmetrically deformed microcavity made of liquid jet. The observed scarred modes correspond to morphology-dependent resonance of radial mode order 3 with their Q values in the range of 10 6 . Emission directionality is also observed, corresponding to a hexagonal unstable periodic orbit. PACS number(s): 05.45.Mt, 42.55.Sa

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(44 citation statements)
references
References 20 publications
(33 reference statements)
4
40
0
Order By: Relevance
“…The corresponding scaling analysis suggested a zero-temperature transition with a critical exponent ν consistent with the value obtained initially from current-voltage scaling 10 . However, a study of the low-temperature configurations for frustrations close the irrational value by MC simulations in the vortex representation 16 , find two phase transitions consistent with earlier work 13 . On the experimental side, some results on arrays of su-perconducting grains at irrational frustration 2,3 are consistent with the scenario of the zero-temperature resistive transition but on wire networks 5,6 , resistivity scaling showed evidence of a transition at finite temperature.…”
Section: -970 São José Dos Campos Sp Brazilsupporting
confidence: 60%
“…The corresponding scaling analysis suggested a zero-temperature transition with a critical exponent ν consistent with the value obtained initially from current-voltage scaling 10 . However, a study of the low-temperature configurations for frustrations close the irrational value by MC simulations in the vortex representation 16 , find two phase transitions consistent with earlier work 13 . On the experimental side, some results on arrays of su-perconducting grains at irrational frustration 2,3 are consistent with the scenario of the zero-temperature resistive transition but on wire networks 5,6 , resistivity scaling showed evidence of a transition at finite temperature.…”
Section: -970 São José Dos Campos Sp Brazilsupporting
confidence: 60%
“…For example modes based on stable periodic ray orbits with bow-tie [4] and triangular geometry [18] have been observed, as well as whispering gallery-like modes [16,18] which are not obviously related to any periodic ray orbit. In addition a periodic orbit mode can be selected for lasing even if it is unstable [17,19,20]; due to the analogy to quantum wavefunctions based on unstable classical periodic orbits, such modes have been termed "scarred" [21]. There is at present no quantitative understanding of the mode selection mechanism in ARCs and theory has tended to work backwards from experimental observations; however the passive cavity solutions have been found to explain quite well the observed lasing emission patterns.…”
Section: Introductionmentioning
confidence: 99%
“…There exist extra and unexpected concentrations, i.e., scars of eigenstate density near unstable periodic orbits. In 2002, Lee et al [49] experimentally observed the scarred modes in asymmetrically deformed microcylinder lasers (liquid jet). This observation is very important since they not only give rise to directional emission but also possess mode-like structures in the emission spectrum.…”
Section: Quadrupole-shaped Arcsmentioning
confidence: 98%